Ecological Insights into the Predatory Behaviour of Condylostylus longicornis in Agricultural Fields of Madurai District, India - Pavunraj, M.; Nagarajan, K.; R.Ramakrishnan; Raja, S.; Murali, P.; Baranitharan, M.; Rajeshkumar, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Researchers affiliated with the Post Graduate and Research Department of Zoology at Vivekananda College in Tiruvedakam West, Madurai, Tamil Nadu, along with collaborators from other institutions, have observed a rare predatory behaviour of long-legged fly Condylostylus longicornis (Diptera: Dolichopodidae) in the agroecosystem of the Sholavandan region in Madurai District, Tamil Nadu. In general, C. longicornis favours environments that are close to marshes, streams, meadows, or forests and that are slightly shaded. C. longicornis is considered an optimal bio-indicator species for monitoring and conserving water quality. This article provides an overview of the history, behavioural characteristics, and ecological significance of C. longicornis.